Internalization of Spiritual Intelligence Values and Emotional Intelligence Values of Post-Islamic Senior High School Students Through the Service Program - Abdur Rochman; Syuhud (Journal of Educational Management Research, 2026)
This study aims to analyze the process and outcomes of internalizing spiritual intelligence and emotional intelligence among post-madrasah aliyah santri through the khidmah program in Islamic boarding school education. This research employed a qualitative approach with a phenomenological design to understand the meaning and experiences of santri in carrying out service-based activities. Data were collected through observation, interviews, and documentation, while the data analysis technique used data condensation, data display, and conclusion drawing/verification to obtain comprehensive findings. The results of the study indicate that the internalization of spiritual and emotional intelligence was carried out through exemplary practices, habituation, value understanding, reflective awareness, and service-oriented responsibilities within the khidmah program. The program successfully fostered religious attitudes, sincerity, discipline, patience, humility, emotional control, cooperation, responsibility, and social awareness among santri. In addition, the khidmah program contributed to the development of independence and emotional maturity through direct interaction and social engagement in daily activities. The implications of this study show that service-based educational programs can become an effective strategy for strengthening holistic character education by integrating spiritual and emotional dimensions in Islamic educational institutions.